Political Influence: Strategies Employed by Organizations to Impact Legislation in Business and Economic Matters - Aplin, John C.; Hegarty, W. Harvey (Academy of Management Journal, 1980)
This study examines strategies that business lobbyists, consumer groups, unions, and federal agencies employ to shape federal legislation. Interviews with U. S. senators and congressmen preceded a questionnaire survey of 435 chief legislative policymakers. Results reveal that the three major sectors adopt different strategy sets and these strategy sets have varying impacts on the legislative process.